Energy Requirement for Failure of Dried Arecanut Fruit and Kernel - AWARE, V.V.; MEHTA, A.K. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
The adequate information on behavior of dried arecanut fruit under different methods of force application like compressive, shear and impact is not available. From this information, the energy and hence the power requirement for dehusking could be calculated. The failure of dried arecanut fruit and kernel in compressive and shear loading were studied using texture analyzer, while impact failure was studied using impact tester. The average power required for dehusking of an arecanut was 18.3 W in compressive loading. In shear loading, it was 107.1 W. In case of arecanut kernel, the power required for axial failure was about double than that of lateral failure. The power required for shear failure of arecanut kernel was only 15.7 W. The power required for dehusking of arecanut fruit in impact loading was 25.5W.